Selection of thermophilic and thermotolerant fungi for the production of cellulases and xylanases under solid-state fermentation - Moretti, Marcia M. S. [UNESP] (2012)
Twenty-seven thermophilic and thermotolerant fungal strains were isolated from soil, decaying organic matter and sugarcane piles based on their ability to grow at 45ºC on medium containing corn straw and cardboard as carbon sources. These fungi were identified in the genera Aspergillus, Thermomyces, Myceliophthora, Thermomucor and Candida. The majority of the isolated strains produced xylanase and cellulases under solid state fermentation (SSF). The highest cellulase and xylanase productions were obtained by the cultivation of the strains identified as Aspergillus fumigatus M.7.1 and Myceliophthora thermophila M.7.7. The enzymes from these strains exhibited maximum activity at pH 5.0 and at 60 and 70ºC. The endo-glucanase from A. fumigatus was stable from 40ºC to 65ºC and both endo-glucanase and xylanase from M. thermophila were stable in this temperature range when in absence of substrate. The enzymes were stable from pH 4.0 to 9.0.